THE RELATIONSHIP BETWEEN CULTURAL BELIEFS AND EXCLUSIVE BREASTFEEDING PRACTICES AMONG POSTPARTUM MOTHERS - Yuli Suryanti; Adhika Wijayanti; Marchatus Soleha; Yan Permadi (LPPM STIKES Al-Ma'arif Baturaja, 2026)
The coverage of exclusive breastfeeding has not yet reached the expected target, despite its well-established benefits for maternal and infant health. Socio-cultural factors, particularly cultural beliefs, are considered important determinants influencing breastfeeding practices among postpartum mothers. This study employed a quantitative design with a cross-sectional approach to analyze the relationship between cultural beliefs and exclusive breastfeeding practices. The research was conducted at PMB Ferawati from October to November 2025, involving 50 postpartum mothers selected through purposive sampling. Data were collected using questionnaires and observation sheets and analyzed using the Chi-Square test. The majority of respondents had negative cultural beliefs (60%) and did not practice exclusive breastfeeding (56%). Among mothers with positive cultural beliefs, 75% practiced exclusive breastfeeding, whereas only 23.3% of mothers with negative cultural beliefs did so. Statistical analysis revealed a significant relationship between cultural beliefs and exclusive breastfeeding (p-value = 0.001). Cultural beliefs are a significant determinant of exclusive breastfeeding practices among postpartum mothers. These findings highlight the importance of culturally sensitive health promotion interventions to improve exclusive breastfeeding coverage sustainably.